Current Approaches for Management of Postpenetrating Keratoplasty Astigmatism. (27th July 2011) - Feizi, Sepehr; Zare, Mohammad
Abstract : A successful corneal graft requires both clarity and an acceptable refraction. A clear corneal graft may be an optical failure if high astigmatism limits visual acuity. Intraoperative measures to reduce postkeratoplasty astigmatism include round and central trephination of cornea with an adequate size, appropriate sutures with evenly distributed tension, and perfect graft-host apposition. Suture manipulation has been described for minimising early postoperative astigmatism. If significant astigmatism remains after suture removal, which cannot be corrected by optical means, then further surgical procedures containing relaxing incisions, compression sutures, laser refractive surgery, insertion of intrastromal corneal ring segments, wedge resection, and toric intraocular lens implantation can be performed. When astigmatism cannot be reduced using one or more abovementioned approaches, repeat penetrating keratoplasty should inevitably be considered. However, none of these techniques has emerged as an ideal one, and corneal surgeons may require combining two or more approaches to exploit the maximum advantages.